Welding method of graded surface structure based on copper crystal

By forming Cu-Ni and Cu-Ag graded surface structures on the welded parts and welding under ultrasonic vibration and pressure, the challenges of surface flatness and defect control of welding pairs in the existing low-temperature welding technology are solved, and defect-free low-temperature welding is achieved, which improves the reliability and application value of welding.

CN119501355APending Publication Date: 2025-02-25GANNAN UNIV OF SCI & TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411987145.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing low-temperature welding technology has challenges in the flatness and defect control of the welding couple surface, especially in three-dimensional chip stacking technology, which requires high welding accuracy and reliability.

Method used

The welding method based on the graded surface structure of copper crystal is adopted, and the Cu-Ni graded structure and Cu-Ag graded structure are formed on the welded parts, and welding is achieved under ultrasonic vibration and pressure to ensure that the interface is free of holes and defects.

Benefits of technology

Achieve defect-free low-temperature welding in a very short time, improve the reliability and application value of welding, reduce damage to the chip function and structure, and maintain good reliability after high-temperature heat treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119501355A_ABST
    Figure CN119501355A_ABST
Patent Text Reader

Abstract

The invention relates to a welding method of a graded surface structure based on copper crystals, and belongs to the technical field of low-temperature welding. The welding method comprises the following steps that needle-cone-shaped Cu micron protrusions are obtained through deposition at the to-be-welded positions of two devices; then, a thorn-shaped Ni nano layer and a cluster-shaped Ag nano layer are deposited on the two needle-cone-shaped Cu micron protrusions respectively, and different welding parts of the two devices are obtained; and contacting the welding part, ultrasonically vibrating the contact surface in the parallel direction for a certain time, applying specific pressure in the vertical direction of the contact surface, and keeping for a certain time to finish welding. By the adoption of the method, welding can be achieved within a very short time without heat treatment and with very low energy consumption, the reliability of a welding interface is excellent, heat damage caused by long-time heat shock borne by electronic elements, especially thin chips in traditional welding is prevented, and the method has very high application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of low temperature welding, and in particular to a welding method based on a graded surface structure of copper crystals. Background Art

[0002] Three-dimensional chip stacking technology can effectively utilize space, reduce volume, reduce costs and energy consumption, and meet the development requirements of miniaturization and high integration of electronic products. However, with the development of technology, the size of devices in stacked packaging continues to decrease, and the size of solder joints also decreases, which puts higher requirements on the existing welding process and interface reliability.

[0003] In the traditional welding process, the melting diffusion welding temperature is high (generally 300-400℃), and the high temperature produces thermal shock to thin chips and heat-sensitive components. The deformation induced by thermal shock greatly reduces the reliability of the package. Under the condition of low-temperature welding, the welding deformation can be controlled and improved, the welding accuracy can be improved, and the manufacturing cost can be reduced. In the prior art, the copper-copper direct welding technology using chemical-mechanical polishing can achieve a firm connection at a lower temperature, but it has extremely high requirements for the flatness of the welding surface. The welding environment is ultra-vacuum, and it is also necessary to anneal for a long time at ultra-high temperature to eliminate holes. The process conditions are harsh and complex, which limits its practical application. If the special micromorphology and size effect of the welding part can be utilized, special properties can be obtained during the welding process, which is easier to extrude and deform, increase the contact area and atomic diffusion area of ​​the welding couple, reduce interface holes, and obtain better welding points under low temperature conditions. However, there is no in-depth exploration of the special morphology low-temperature rapid welding process steps in the prior art.

[0004] Therefore, optimizing and developing a low-temperature and fast welding method based on nanoscale graded surface structure will play an important role in promoting the development of three-dimensional chip stacking technology. Summary of the invention

[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a welding method based on a graded surface structure of copper crystals. The method provided by the present invention can achieve welding without hole defects on the interface in a very short time and under low temperature conditions, with excellent welding reliability and high application value.

[0006] To achieve the above object, the technical solution adopted by the present invention is:

[0007] In a first aspect, the present invention provides a welding method based on a hierarchical surface structure of copper crystals, comprising the following steps:

[0008] (1) performing deposition once at the locations to be welded of the first welded part and the second welded part respectively, to obtain needle-cone-shaped Cu micron protrusions;

[0009] (2) depositing a thorn-shaped Ni nanolayer on the needle-cone-shaped Cu micron protrusion of the first welding part for the second time to obtain a first welding part; the thorn-shaped Ni nanolayer includes a Ni deposition layer, a first Ni protrusion, and a second Ni protrusion in sequence;

[0010] (3) depositing a clustered Ag nanolayer on the needle-cone-shaped Cu micron protrusion of the second welding part three times to obtain a second welding part; the clustered Ag nanolayer includes an Ag deposition layer and an Ag protrusion in sequence;

[0011] (4) The first welding part is brought into contact with the second welding part, ultrasonically vibrated in a direction parallel to the contact surface, pressurized in a direction perpendicular to the contact surface to a welding pressure, and welded to complete the welding of the graded surface structure based on copper crystals; the ultrasonic vibration time is 2.5-3.5s, the welding pressure is 7000-9000gf, and the welding time is 2.5-3.5s.

[0012] The present invention provides a low-temperature welding method, which is based on the Cu-Ni graded surface structure and the Cu-Ag graded surface structure obtained by deposition: the method provided by the present invention first forms a Cu micron-protrusion structure at two to-be-welded locations of a welded part, and then continues to deposit a Ni nanolayer with a thorn-shaped appearance (including a bottom deposition layer and a Ni protrusion with a top secondary structure) to obtain the Cu-Ni graded surface structure as one side of a welding couple (a first welding portion); and deposits a clustered Ag nanolayer with an appearance of imitating a lotus leaf surface (including a bottom deposition layer and a top protrusion portion) on the copper micron-protrusion structure at another to-be-welded location to obtain the Cu-Ag graded surface structure as the other side of the welding couple (a second welding portion).

[0013] Under room temperature conditions, under the above-mentioned specific pressure and ultrasonic vibration, the two welding parts are brought into contact, and the welding of the welding parts can be achieved in a very short time of a few seconds. Under specific ultrasonic vibration, the thorn-like Ni nanolayer and the clustered Ag nanolayer can cause lateral friction; and the contacting structures based on the copper graded surface are squeezed and embedded into each other as a whole under the vertical pressure, and plastic deformation or fracture occurs, realizing low-temperature and low-energy welding without interface defects. When the ultrasonic time, welding pressure or welding time is not suitable, it may cause hole defects, cracks, deformations in the welding interface, or affect the structural reliability of the welded part itself, and damage the structural performance of the device.

[0014] The special morphology of the above-mentioned graded surface structure promotes the interface diffusion reaction and increases the diffusion area of ​​Ag and Ni atoms. For the clustered Ag nanolayer, the friction energy generated by ultrasonic transverse nonlinear vibration causes the welding interface to heat up rapidly. The clustered Ag nanolayer has a high surface meltability due to the nanometer size effect. It can quickly connect to the surrounding structure during the ultrasonic friction heating process and has excellent sintering performance. The Ag layer softens and melts under the dual effects of heat and vertical pressure. At this time, the thorny Ni nanolayer with higher hardness can be more easily inserted into the softened clustered Ag nanolayer. At the same time, ultrasound accelerates the solid-liquid reaction, and the welding interface accelerates the reaction to generate a solid solution, forming solid solution strengthening, and the welding process is quickly completed within a few seconds. As a welding intermediate layer, it also plays a buffering role, thereby obtaining a defect-free welding interface and reducing the damage to the chip function and structure during the welding process.

[0015] The welding interface formed by the welding method provided by the present invention, after 200h of long-term high-temperature heat treatment (160°C), is a defect-free welding interface that will not produce new holes, and the reliability of the interface is excellent. In addition, the welding method of the present invention does not require an additional heat treatment process to increase the strength of the welding interface, and still maintains good reliability performance during subsequent use. At the same time, due to the specific special morphology and intermediate layer buffering effect of the Cu-Ni graded surface structure and the Cu-Ag graded surface structure formed on both sides of the welding couple, as well as the introduction of ultrasonic waves, defect-free welding can be completed in an instant at room temperature, avoiding thermal damage caused by long-term thermal shock to electronic components, especially thin chips. Compared with the high temperature required for reflow soldering, the present invention does not require complex processes such as ultra-high vacuum and ultra-high surface flatness, and the welding conditions are more relaxed and the energy consumption is low. It conforms to the development trend of green packaging, has a good comprehensive effect, and has huge application potential.

[0016] Preferably, the primary deposition is copper electroplating, and the current density of the primary deposition is 7.5-8.5 A / dm 2 , the electroplating time is 18-22 minutes; the copper electroplating solution deposited once includes 1.4-1.6 g / L PEG.

[0017] Preferably, the welded parts are degreased, acid treated and activated before being electroplated.

[0018] Further preferably, the formula of the copper electroplating solution is: main salt CuSO 4 ·5H 2 O(12g / L), NiSO 4 ·5H 2 O (1.3 g / L), buffer H 3 BO 3 (22g / L), reducing agent Na 3 C 6 H5 O 7 (22g / L), NaH 2 PO 2 (30 g / L), crystal modifier PEG (1.5 g / L), and NaOH (8.5 g / L).

[0019] In one deposition, by using the above-mentioned crystal modifier PEG and controlling the deposition current density and time conditions, the appropriate needle-cone-shaped Cu micron protrusion structure morphology and size can be controlled. The obtained Cu-Ni hierarchical structure and Cu-Ag hierarchical structure still maintain the conical protrusion structure.

[0020] Preferably, the average height of the needle-cone-shaped Cu micron protrusions is 4-6 μm, and the average root diameter is 0.8-1.2 μm.

[0021] In order to obtain good welding effect in subsequent processes, the needle-cone-shaped Cu micron-protrusion structure needs to have a large bottom diameter to ensure shear strength; the top angle should be small to easily produce a tip effect, which is conducive to insertion and mechanical inlay effect during welding; under the above-mentioned appropriate electroplating conditions, the height and distribution of the protrusion structure are uniform and relatively consistent.

[0022] Preferably, the secondary deposition is nickel electroplating, and the specific process is as follows:

[0023] First, at a current density of 0.02-0.04A / cm 2 Deposition was performed for 13-17 min at a current density of 0.05-0.07 A / cm 2 Deposition for 2-2.5min;

[0024] The secondary deposition nickel plating solution includes 90 g / L ethylenediamine dihydrochloride.

[0025] Preferably, the needle-cone-shaped Cu micron-protrusion structure is polished and pickled before the nickel electroplating.

[0026] Preferably, the pH of the nickel electroplating solution is 4.0 and the temperature is 65°C.

[0027] Further preferably, the formula of the nickel electroplating solution is: NiCl 2 6H 2 O(5-200g / L), H 3 BO 3 (30g / L), crystal modifier ethylenediamine dihydrochloride (90g / L).

[0028] The above-mentioned plating solution formula, deposition parameters and additive types determine the appropriate morphology and thickness of the nodular Ni nanolayer.

[0029] Preferably, the average thickness of the Ni deposition layer is 180-220 nm; the average height of the first Ni protrusion is 450-550 nm, and the average root diameter is 350-450 nm; the height of the second Ni protrusion is 50-100 nm.

[0030] Preferably, the three depositions are chemical silver plating, the pH of the chemical silver plating solution is 9-10, the temperature is 50-70° C., and the deposition time is 20-40 min.

[0031] Preferably, the needle-cone-shaped Cu micron-protrusion structure is polished and pickled before the chemical silver plating.

[0032] Preferably, the chemical silver plating solution formula is: AgNO 3 (0.05mol / L), Na 2 S 2 O 3 (0.06mol / L), K 2 S 2 O 5 (0.01-0.04mol / L), CH 3 COONH 4 (0.001-0.004mol / L).

[0033] Preferably, the average thickness of the Ag deposition layer is 180-220 nm, and the average diameter of the Ag protrusions is 150-250 nm.

[0034] As a buffer layer, the Ag layer cannot be too thin, otherwise it cannot fill the holes between the hierarchical structures through deformation; combined with Ag's anti-electromigration ability, it cannot be too thick. The bottom of the protruding structure is covered with a nano-Ag particle deposition layer, showing good profiling and coverage. As the deposition time increases from 10min to 30min, the diameter of the nano-Ag particles increases from 70nm to 200nm, and a cluster structure of larger particles is formed on the surface of the thorn-like Ni nanolayer structure. This micro-nano composite structure looks similar to the surface structure of a lotus leaf. When the deposition time is too long, the Ag nanoparticles fill the protruding surface to form a thick coating, the secondary structure disappears, and the special morphology cannot be achieved.

[0035] Preferably, the frequency of the ultrasonic vibration is 25-35 KHz.

[0036] Preferably, the moving speed of the pressurizing pressure head is 0.04-0.06 mm / s.

[0037] Preferably, the ultrasonic vibration time is 3 s, the welding pressure is 8000 gf, and the welding time is 3 s.

[0038] Under the optimal welding conditions, high-quality welded products with the best welding interface and no defects can be obtained. After long-term heat treatment, the welding interface morphology will not change significantly and no obvious holes will be generated. The interface has high reliability and still maintains good reliability performance during subsequent use.

[0039] Compared with the prior art, the present invention has the following beneficial effects:

[0040] The invention provides a welding method based on a graded surface structure of copper crystals. Firstly, a Cu-Ni graded structure and a Cu-Ag graded structure with specific morphology are formed on a welded part, so as to improve welding efficiency and reduce damage to chip function and structure during the welding process. Then, welding is achieved through ultrasonic vibration and pressure treatment. By optimizing welding pressure, welding time and ultrasonic treatment time parameters during the low-temperature welding process, problems such as holes and gaps on the welding base surface, cracks, structural deformation of the welded part, and performance impairment can be avoided, so that a defect-free welding interface is achieved, and the reliability of the package is excellent. The reliability is still good after high-temperature treatment, and the method has great application potential. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 This is a SEM image of the needle-cone-shaped Cu micron protrusion formed by the welding method based on the hierarchical surface structure of copper crystals in Example 1;

[0042] Figure 2 This is a SEM image of a thorny Ni nanolayer formed by a welding method based on a hierarchical surface structure of copper crystals in Example 1;

[0043] Figure 3 This is a TEM image of a thorny Ni nanolayer formed by a welding method based on a hierarchical surface structure of copper crystals in Example 1;

[0044] Figure 4 This is a SEM image of a clustered Ag nanolayer formed by a welding method based on a hierarchical surface structure of copper crystals in Example 1;

[0045] Figure 5 This is a TEM image of a clustered Ag nanolayer formed by a welding method based on a hierarchical surface structure of copper crystals in Example 1;

[0046] Figure 6 This is a welding schematic diagram of a welding method based on a graded surface structure of copper crystals in Example 1;

[0047] Figure 7 This is a morphology diagram of a welding interface formed by a welding method based on a graded surface structure of copper crystals in Example 1;

[0048] Figure 8 This is a SEM image of the clustered Ag nanolayer formed by the welding method of Comparative Example 1;

[0049] Fig. 9 This is a morphology diagram of the welding interface formed by the welding method of Comparative Example 2;

[0050] Fig.10 This is a morphology diagram of the welding interface formed by the welding method of Comparative Example 3;

[0051] Fig.11 This is a morphology diagram of the welding interface formed by the welding method of Comparative Example 4;

[0052] Fig.12 This is a morphology diagram of the welding interface formed by the welding method of Comparative Example 5;

[0053] Fig.13 This is a morphology diagram of the welding interface formed after heat treatment for 2 hours based on the welding method of hierarchical surface structure of copper crystals in Example 1;

[0054] Fig.14 This is a morphology diagram of the welding interface formed after heat treatment for 20 hours based on the welding method of hierarchical surface structure of copper crystals in Example 1;

[0055] Fig.15 This is a morphology diagram of the welding interface formed after heat treatment for 200 hours in the welding method based on the hierarchical surface structure of copper crystals in Example 1;

[0056] Fig.16 This is a morphology diagram of the welding interface formed after heat treatment for 2 hours after welding according to the welding method of comparative example 6;

[0057] Fig.17 This is a morphology diagram of the welding interface formed after heat treatment for 20 hours after welding according to the welding method of comparative example 6;

[0058] Fig.18 This is a morphology diagram of the welding interface formed after heat treatment for 200 hours after welding according to the welding method of comparative example 6;

[0059] Fig.19 This is a low-magnification TEM image of a welding interface formed by a welding method based on a hierarchical surface structure of copper crystals in Example 1;

[0060] Fig. 20 This is a high-magnification TEM image of a welding interface formed by a welding method based on a hierarchical surface structure of copper crystals in Example 1;

[0061] Fig.21 A high-resolution phase image of a high-magnification TEM region 1 of a welding interface formed by a welding method based on a hierarchical surface structure of copper crystals in Example 1;

[0062] Fig. 22 This is a high-resolution phase image of a high-magnification TEM region 2 of a welding interface formed by a welding method based on a hierarchical surface structure of copper crystals in Example 1. DETAILED DESCRIPTION

[0063] In order to better illustrate the purpose, technical scheme and advantages of the present invention, the present invention will be further described below in conjunction with specific examples. The test methods used in the following examples are conventional methods unless otherwise specified; the materials and reagents used are reagents and materials that can be obtained from commercial channels unless otherwise specified.

[0064] Example 1

[0065] An embodiment of the welding method based on the graded surface structure of copper crystals of the present invention is as follows:

[0066] (1) Select the lead frame material C194 as the part to be welded, cut it into two 50mm*50mm squares, and use 8A / dm 2 The samples were degreased at a current density of 1000 nm for 30 min, immersed in a 10% sulfuric acid solution for 20 s, activated in a palladium chloride solution (concentration 0.001 mol / L) for 60 s, and finally deposited in a plating solution. The formula of the plating solution was: main salt CuSO 4 ·5H 2 O(12g / L), NiSO 4 ·5H 2 O (1.3 g / L), buffer H 3 BO 3 (22g / L), reducing agent Na 3 C 6 H 5 O 7 (22g / L), NaH 2 PO 2 (30g / L), crystallization regulator PEG (1.5g / L), NaOH (8.5g / L), electrodeposition time is 20min, and needle-cone-shaped Cu micron protrusions are obtained; the device containing the needle-cone-shaped Cu micron protrusion structure is electrochemically polished and pickled for 30s before subsequent operations.

[0067] (2) A 99.9% Ni plate (size 60 mm × 150 mm × 3 mm) was used as the anode, and Ni was electroplated on the needle-cone-shaped Cu micron protrusions using a two-step process: the formula of the nickel electroplating solution was: NiCl 2 6H 2 O(5-200g / L), H 3 BO 3(30g / L), crystal modifier ethylenediamine dihydrochloride (90g / L), solvent is deionized water, pH of the solution is adjusted to 4.0 by adding HCl or NaOH, and the plating temperature is 65°C. First, at a lower current density (0.03A / cm 2 ) deposition time of 15 min, and then at a higher current density (0.06 A / cm 2 ) for 2 minutes to obtain a thorny Ni nanolayer and obtain the first welding part.

[0068] (3) Chemical plating is performed on the needle-cone-shaped Cu micron protrusions, and the composition of the plating solution is: AgNO 3 (0.05mol / L), Na 2 S 2 O 3 (0.06mol / L), K 2 S 2 O 5 (0.025mol / L), CH 3 COONH 4 (0.0025mol / L), the pH value of the plating solution was adjusted to 9-10 with ammonia water, the plating solution temperature was controlled at 50-70°C, the deposition time was 30min, a clustered Ag nanolayer was obtained, and a second welding part was obtained.

[0069] (4) A customized ultrasonic micro spot welding machine (Rhesca PTR-1102) was used, the ultrasonic fixed frequency was set to 30 kHz, and the welding parameters were precisely controlled by a computer, as follows:

[0070] A copper substrate with a Cu-Ag graded surface structure plated on the surface is placed on a sample stage of a welding machine and fixed, with the second welding portion facing upward, and a copper substrate with a Cu-Ni graded surface structure plated on the surface is placed thereon with the first welding portion facing downward, so that the graded surface structures are in contact with each other;

[0071] Shake the handle to adjust the position of the sample stage so that the pressure head is aligned with the center of the upper substrate to ensure uniform ultrasonic vibration and pressure; adjust the height of the pressure head and stop it at a distance of 0.2mm from the copper substrate above the welding couple; start the welding program, and the pressure head descends at a speed of 0.05mm / s until it contacts the upper copper substrate, start to increase the vertical welding pressure, start ultrasound at the same time and record the ultrasonic time (set to 3s);

[0072] The pressure and ultrasonic vibration are transmitted to the copper substrate above the welding couple through the pressure head. When the welding pressure reaches the set value of 8000gf (5MPa), the welding time begins to be recorded. When the welding time reaches the set value of 3s, the pressure head is lifted and returns to the initial position, and the welding procedure ends, realizing welding based on the graded surface structure of copper.

[0073] The SEM structure of the needle-cone-shaped Cu micron protrusion obtained in the above step (1) is as follows: Figure 1 , it can be seen that the average height of the needle-cone-shaped Cu micron protrusions is about 5 μm, and the average root diameter is about 1 μm.

[0074] The SEM image of the thorn-like Ni nanolayer obtained in step (2) is as follows: Figure 2 , TEM images Figure 3 It can be seen that the thorn-like Ni nanolayer is nano-nano in size, and the thickness of the bottom Ni deposition layer is about 200nm; the height of the first layer of Ni protrusions is about 500nm, and the root diameter is about 400nm; the second Ni protrusion is a secondary Ni protrusion with a smaller vertex angle and a height of 50-100nm. At the same time, the results of XRD show that the preferred orientations of Cu and Ni are (220) and (111), respectively. This is because the protrusions in the Cu-Ni graded surface structure of the first welding part are dense and super hydrophobic.

[0075] The SEM image of the clustered Ag nanolayer obtained in step (3) is as follows: Figure 4 TEM images Figure 5 As the Ag deposition time increases from 10 min to 30 min, the diameter of the nano-Ag particles gradually increases from 70 nm to 200 nm, and a cluster structure of larger particles is formed on the surface of the Cu micron-protrusion structure. This micro-nano composite structure is similar to the surface structure of a lotus leaf, and the thickness of the Ag deposition layer is about 180 nm.

[0076] The schematic diagram of welding in the above step (4) is as follows Figure 6 The morphology of the welding interface formed after welding is as follows: Figure 7 It can be seen that when the welding pressure is 8000gf, the welding time is 3s, and the ultrasonic vibration is 3s, in the welding interface of the Cu-Ni graded surface structure of the first welding part and the Cu-Ag graded surface structure of the second welding part, the upper and lower structures of the welding couple are in contact with each other, the top part is deformed, and the hole is filled with the Ag layer. The Cu / Ni / Ag / Cu sandwich structure of the welding interface is uniform in the horizontal direction, and the structures on both sides are embedded in each other to form a mechanical interlocking effect; Ni and Ag are fused with each other, and there are no obvious defects such as holes in the welding interface. The welding interface forms an effective connection and has good bonding reliability.

[0077] Comparative Example 1

[0078] The difference between Comparative Example 1 and Example 1 is that the deposition time in step (3) is 60 min, and the structure of the clustered Ag nanolayer is as follows: Figure 8 , it can be seen that the Ag particles fill the surface of the needle-cone-shaped Cu micron protrusions, forming an overly thick coating, and the secondary structure disappears.

[0079] Comparative Example 2

[0080] The difference between Comparative Example 2 and Example 1 is that the setting value of the welding pressure in step (4) is 2000 gf. The morphology of the welding interface formed after welding is as follows: Fig. 9 .

[0081] It can be seen that due to the small pressure, there is an obvious gap between the graded structures of the welding parts on both sides, and no effective connection is formed; and it is found that the top parts of some graded surface structures are slightly tilted and deformed. This is because the welding pressure is too small, and the graded surface structures on both sides have height differences. Under pressure, the graded structure with a higher height produces a slight contact deformation and has not yet formed a connection point. Therefore, after the pressure is unloaded, the copper-based structures on both sides are separated again.

[0082] Comparative Example 3

[0083] The difference between Comparative Example 3 and Example 1 is that the setting value of the welding pressure in step (4) is 4000 gf. The morphology of the welding interface formed after welding is as follows: Fig.10 .

[0084] It can be seen that the graded surface structures on both sides are in contact with each other. Due to the height difference of the graded structures, the top of the Cu-Ag graded surface structure is squeezed and deformed greatly during the insertion of the Cu-Ni graded surface structure. Some tip parts are broken and scattered at the welding interface. Some Cu-Ag graded surface structures with relatively low heights do not contact the Cu-Ni graded surface structure, resulting in holes. Almost no holes are found between the graded structures of the first welding part on the upper side. This is because the holes are eliminated by copper deformation and filling of clustered Ag nanolayers. The thorn-like Ni nanolayer has a higher hardness difference compared with Cu and Ag due to the tip effect, nanosize effect and high hardness. The harder Ni nanolayer is easy to insert into the softer Cu-Ag graded surface structure. Observing the welding interface, it is found that the size of the holes and deformation of the upper and lower structures is quite different. This is because the welding pressure is insufficient, the graded surface structures on the upper and lower sides are not in complete contact, and the pressure conduction and ultrasonic conduction are insufficient.

[0085] Comparative Example 4

[0086] The difference between Comparative Example 4 and Example 1 is that the setting value of the welding pressure in step (4) is 10000 gf. The morphology of the welding interface formed after welding is as shown in FIG. Fig.11 .

[0087] It can be seen that although the graded surface structures on the upper and lower sides are tightly connected together, there is serious bending deformation at the welding interface, the surface structure is deformed at the micron level, the high pressure causes structural damage to the electronic devices, the welding quality is unreliable, and the function of the electronic devices is adversely affected.

[0088] Comparative Example 5

[0089] The difference between Comparative Example 5 and Example 1 is that the setting value of the welding pressure in step (4) is 10000 gf, the welding time is 2 s, the ultrasonic time is 2 s, and the welding interface morphology formed after welding is as shown in FIG. Fig.12 .

[0090] It can be seen that the welding time is too short, and the graded surface structures on both sides do not have enough time to complete the embedding and interlocking after contact. Under the high pressure of 10000gf, the Ni layer and the Ag layer contact each other but no effective welding point is formed. The thorn-like Ni nanolayer and the clustered Ag nanolayer contact and squeeze each other under the pressure of 10000gf, and the ultrasonic action produces lateral friction. After a short welding time, the graded surface structures on both sides of the welding couple are separated, and there are obvious lateral cracks. The fracture direction of the top of the graded surface structure is consistent, which is caused by the lateral vibration applied by the ultrasonic wave.

[0091] Comparative Example 6

[0092] The only difference between Comparative Example 6 and Example 1 is that in step (4), the welding time is controlled to be 2 s and the ultrasonic time is controlled to be 2 s.

[0093] It can be observed that when the welding time is reduced to 2 s and the ultrasonic time is reduced to 2 s, under the condition of less than 10000 gf, the graded surface structures of the welding parts on both sides cannot be welded together.

[0094] Comparative Example 7

[0095] The difference between Comparative Example 7 and Example 1 is that the setting values ​​of the welding pressure in step (4) are 4000 gf, 8000 gf, and 10000 gf, respectively, the welding time is 4 s, and the ultrasonic time is 4 s.

[0096] It can be observed that when the welding pressure is 4000 gf, the welding time is 4 s, and the ultrasonic is 4 s, the top of the graded surface structure is severely deformed, and there is a coarse transverse crack in the middle of the welding interface;

[0097] When the welding pressure is 8000gf, the welding time is extended to 4s, and the ultrasonic is 4s, there are small transverse cracks on the welding interface, the welding interface undergoes slight deformation, and the welding interface still has defects. Due to the long welding time and the long transverse vibration time of the welding interface, linear cracks are generated.

[0098] When the welding pressure increases to 10000gf, the welding interface deforms greatly. Although a tight connection is achieved, the structural reliability of the electronic components is affected;

[0099] When the welding time and ultrasonic time are extended to 4s, the welding time has a greater impact on the welding interface morphology than the welding pressure. When the welding pressure is below 8000gf, transverse linear cracks will occur. When the welding pressure is greater than 10000gf, the welding interface will be significantly deformed, damaging the device structure performance.

[0100] Based on the observation of the welding interface in the above embodiments and comparative examples, it can be known that under specific welding pressure conditions, a good welding interface can be obtained, and the welding time has a critical value. When the welding time is less than the specified range of the present invention, even if the welding pressure is increased, a firm welding point cannot be obtained, so the welding time is too short to obtain effective welding; and when the welding time is extended to exceed the specified range of the present invention (4s), if the welding pressure is less than 4000gf, the tip part of the graded surface structure has serious plastic deformation and cannot form effective welding; if the welding time is too long and the welding pressure is 8000-10000gf, transverse linear cracks will be generated due to the long ultrasonic transverse friction time; when the welding pressure continues to increase to more than 10000gf, there is no gap in the welding interface, but serious deformation will occur. Therefore, in order to obtain an excellent defect-free welding interface, the optimal process parameters of the present invention are welding pressure 8000gf, welding time 3s, and ultrasonic time 3s.

[0101] Effect Example 1

[0102] In order to explore the influence of heat treatment on the welding interface formed by the welding method based on the hierarchical surface structure of copper crystals of the present invention, the following heat treatment test was carried out:

[0103] The welded parts with defect-free welding interfaces in Example 1 and the defective parts in Comparative Example 6 were heat treated at 160° C. for different time periods: 2 h, 20 h, and 200 h, and the morphologies of the welding interfaces were observed.

[0104] The weld interface morphologies of the welded parts treated for 2h, 20h, and 200h in Example 1 are as follows: Figure 13-15. It can be seen that the heat treatment did not cause a significant change in the morphology of the welding interface, no obvious holes were found at the welding interface, and the boundary between the Ag-Ni alloy and the copper substrate tended to become blurred, indicating that the diffusion of Ag-Ni atoms was more obvious. This is because the thickness of the Ni layer and the Ag layer is relatively thin, about 200nm. During the welding process, under the dual effects of instantaneous heat generation from ultrasonic lateral vibration friction and vertical pressure, Ag and Ni dissolved each other to form an alloy. No phase change reaction occurred at 160°C, the composition of the welding interface was stable, and no other intermetallic compounds were generated; but after a long period of high-temperature heat treatment, the diffusion of Ag and Ni atoms made the interface with the copper substrate blurred. This shows that heat treatment at 160°C will not cause new holes in the defect-free welding interface, and the reliability of the interface will not be reduced. The welding method provided by the present invention has excellent reliability, does not require an additional heat treatment process to increase the strength of the welding interface, and still maintains good reliability performance during subsequent use.

[0105] The weld interface morphologies of the welded parts treated for 2h, 20h, and 200h in Comparative Example 6 are as follows: Figure 16-18 . It can be seen that under the welding process parameters of 8000gf, welding time and ultrasonic time of 2s, a welding interface with transverse cracks is obtained: at 160℃, after 2h, 20h, and 200h of heat treatment, the morphology of the transverse crack in the middle of the welding interface does not change significantly, and the crack does not become smaller or disappear; this shows that the heat treatment process cannot eliminate the transverse cracks through atomic diffusion; after 20h of heat treatment, new diffusely distributed micro-voids appear inside the Ag-Ni alloy. It is speculated that some areas in the welding interface have not yet formed Ag-Ni alloy due to insufficient diffusion, and still maintain the cluster Ag nanolayer area. During the high-temperature heat treatment process, the original Ag cluster layer undergoes sintering and solidification deformation to produce Kirkendall holes. With the increase of subsequent heat treatment time, the area where sintering and solidification can occur at the welding interface continues to increase, and the size and number of holes tend to expand continuously. Heat treatment tests show that transverse cracks at the welding interface cannot be eliminated by heat treatment processes. On the contrary, as the heat treatment time increases, new hole defects will be generated at the welding interface, threatening the reliability of welding quality.

[0106] Effect Example 2

[0107] In order to explore the influence of the interface reaction on the bonding strength and reliability of the welding interface in the welding method based on the hierarchical surface structure of the copper crystal of the present invention, the TEM morphology of the welding interface after ion thinning after welding in the embodiment is observed by TEM image, and its atomic diffusion is analyzed. Under the welding process conditions of Example 1, the welding interface is relatively firmly bonded, and there are no obvious holes and cracks, which can better study the vertical pressing process and interface reaction of the welding point.

[0108] Fig.19 This is a low-magnification TEM image of the welding interface of Example 1. The complete morphology of the Cu micron-protrusion structure on both sides of the welding interface can be clearly seen in the field of view. The welding interface still maintains a state similar to the insertion of needles and cones, and its shape is outlined by some lines with relatively bright contrast. The area where those lines with relatively bright contrast are located is the Ni-Ag solid solution area.

[0109] Fig. 20 This is a high-magnification TEM image of the welding interface of Example 1. It can be clearly seen that the interface of the Cu-Ni micro-nano hierarchical structure on the left is inserted into the Cu-Ag micro-nano hierarchical structure on the right. The Ni-Ag bonding areas are scattered along the contour of the Cu micron-protruding structure, showing bright areas. The Ni layer on the tip surface of the Cu micron-protruding structure on the left is connected to the clustered Ag on the right, and they are plastically deformed, sintered and squeezed together under the action of ultrasound and vertical pressure. Due to the difference from the copper contrast, it can be clearly seen that the Ni layer on the tip surface of the Cu micron-protruding structure on the left is very tightly bonded to the clustered Ag on the right after extrusion deformation, and almost no holes are seen, indicating excellent welding quality. The two areas in the middle of the connection on both sides were selected for further observation, and the results are as follows Fig.21 , 22 .

[0110] Under the dual effects of ultrasonic friction and pressure embedding, Fig.21 and Fig. 22 The rapid diffusion of Ni / Ag and Ag / Cu can be seen in the high-resolution phases of different regions. By measuring the interplanar spacing, the lattice fringes of Ag(110), Ni(-112), and Cu(111) can be tracked at the welding interface. Fig.21 To approach region 1 of the Cu-Ni hierarchical surface structure, Ni and Ag can be traced, with their distances differing by only a few nanometers. Fig. 22 In the 2nd area close to the Cu-Ag graded surface structure, there is single substance Ag. During the 3s ultrasonic welding time, the atomic diffusion is limited, and Ag cannot completely become a solid solution. In addition, due to the dual effects of friction and compression during the welding process, the Ag atoms present multiple orientations. Fig.21 and Fig. 22 Some amorphous areas where lattice fringes intersect can also be found, and there are atomic-level connections on the surface, which ensures the strength of the welding interface. Fig. 20 The selected area electron diffraction pattern at the location of the Cu nano-protrusion structure is marked as the

[110] crystal zone axis of Cu, indicating that the Cu micro-protrusion still maintains the original needle-cone structure after welding.

[0111] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A welding method based on a graded surface structure of copper crystals, characterized in that: The following steps are involved: (1) performing deposition once at the locations to be welded of the first welded part and the second welded part respectively, to obtain needle-cone-shaped Cu micron protrusions; (2) depositing a thorn-shaped Ni nanolayer on the needle-cone-shaped Cu micron protrusion of the first welding part for the second time to obtain a first welding part; the thorn-shaped Ni nanolayer includes a Ni deposition layer, a first Ni protrusion, and a second Ni protrusion in sequence; (3) depositing a clustered Ag nanolayer on the needle-cone-shaped Cu micron protrusion of the second welding part three times to obtain a second welding part; the clustered Ag nanolayer includes an Ag deposition layer and an Ag protrusion in sequence; (4) The first welding part is brought into contact with the second welding part, ultrasonically vibrated in a direction parallel to the contact surface, pressurized in a direction perpendicular to the contact surface to a welding pressure, and welded to complete the welding of the graded surface structure based on copper crystals; the ultrasonic vibration time is 2.5-3.5s, the welding pressure is 7000-9000gf, and the welding time is 2.5-3.5s.

2. The welding method based on the hierarchical surface structure of copper crystals according to claim 1, characterized in that: The primary deposition is copper electroplating, and the current density of the primary deposition is 7.5-8.5A / dm 2 , the electroplating time is 18-22 minutes; the copper electroplating solution deposited once includes 1.4-1.6 g / L PEG.

3. The welding method based on the hierarchical surface structure of copper crystals according to claim 1, characterized in that: The average height of the needle-cone-shaped Cu micron protrusions is 4-6 μm, and the average root diameter is 0.8-1.2 μm.

4. The welding method based on the hierarchical surface structure of copper crystals according to claim 1, characterized in that: The secondary deposition is nickel electroplating, and the specific process is as follows: First, at a current density of 0.02-0.04A / cm 2 Deposition was performed for 13-17 min at a current density of 0.05-0.07 A / cm 2 Deposition for 2-2.5min; The secondary deposition nickel plating solution includes 90 g / L ethylenediamine dihydrochloride.

5. The welding method based on the hierarchical surface structure of copper crystals according to claim 1, characterized in that: The average thickness of the Ni deposition layer is 180-220nm; the average height of the first Ni protrusion is 450-550nm, and the average root diameter is 350-450nm; the height of the second Ni protrusion is 50-100nm.

6. The welding method based on the hierarchical surface structure of copper crystals according to claim 1, characterized in that: The three depositions are chemical silver plating, the pH of the chemical silver plating solution is 9-10, the temperature is 50-70° C., and the deposition time is 20-40 min.

7. The welding method based on the hierarchical surface structure of copper crystals according to claim 1, characterized in that: The average thickness of the Ag deposition layer is 180-220 nm, and the average diameter of the Ag protrusion is 150-250 nm.

8. The welding method based on the hierarchical surface structure of copper crystals according to claim 1, characterized in that: The frequency of the ultrasonic vibration is 25-35KHz.

9. The welding method based on the hierarchical surface structure of copper crystals according to claim 1, characterized in that: The moving speed of the pressurized pressure head is 0.04-0.06 mm / s.

10. The welding method based on the hierarchical surface structure of copper crystals according to claim 1, characterized in that: The ultrasonic vibration time is 3s, the welding pressure is 8000gf, and the welding time is 3s.